Menelaah Narasi Kebijakan Pajak Daerah Dalam UU No. 1 Tahun 2022: Sebuah Tinjauan Literatur - Chessa Ario Jani Purnomo; Isnu Harjo Prayitno; Dian Ekawati (Faculty of Law, Andalas University, 2022)
The development of a local tax system is one of the policy themes of Law No. 1 of 2022. However, Law No. 1 of 2022 focuses exclusively on material tax law, such as adjustments to local tax tariffs, and makes no reference to formal tax law, such as the renewal of regional tax collecting methods. Whereas tax law can theoretically be classified into two categories, namely material tax law and formal tax law. The article employs a legal doctrinal method with a conceptual approach. This article advances the theoretical argument that fiscal decentralization is top-down in nature, that changes in local tax policy are made purely to fulfil national fiscal objectives, not to build regional tax systems in response to regional efforts. The paper begins with a discussion of fiscal decentralization, the policy narrative underlying Law No. 1 of 2022, and the pressing need to change municipal tax collecting policies. The study concludes that there is a policy imperative to strengthen municipal tax collection rules to keep pace with the policy environment's evolution in the digital and internet+ (internet plus)